The Review of Islamic Law on the Distribution of Zakat Directly by Muzaki to Mustahik in the Sunan Ampel Religious Tourism Area in Surabaya - Febriyanti, Novi (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2020)
BAZ/LAZ was formed as an implementation of zakat management objectives so that it runs well and professionally. Through this research, it can be seen how the implementation of zakat distribution in the Muslim community in carrying out zakat payments and the various factors that cause the Muslim community who is obliged to do zakat to choose to distribute zakat directly to mustahik. Related to this type of research, the researcher used descriptive qualitative research with sociological and empirical approaches. In this study, researchers took the research object in the Sunan Ampel Religious Tourism Area in Surabaya. From the results of this study it can be concluded that the pattern of zakat distribution in the Muslim community occurs in two policies, namely following the BAZ/LAZ policy and the policies pursued through the direct distribution of zakat. The factors causing direct distribution of zakat occur due to the lack of socialization of the latest laws, the long distance from BAZ/LAZ, lack of trust and muzakki feel that they are more affluent and practically pay zakat themselves. The emergence of these reasons, it can be said that the management of zakat is included in the distribution of zakat illegally and violates the law due to a lack of coordination in the management of zakat.